Activation‐induced deaminase–deficient MRL/lpr mice secrete high levels of protective antibodies against lupus nephritis - Jiang, Chuancang; Zhao, Ming‐Lang; Scearce, Richard M.; Diaz, Marilyn (Arthritis & Rheumatism, 2011)
Objective We previously generated MRL/lpr mice deficient in activation‐induced deaminase (AID) that lack isotype switching and immunoglobulin hypermutation. These mice have high levels of unmutated (germline) autoreactive IgM, yet they experienced an increase in survival and an improvement in lupus nephritis that exceeded that of MRL/lpr mice lacking IgG. The purpose of the present study was to test the hypothesis that high levels of germline autoreactive IgM in these mice confer protection against lupus nephritis. Methods Autoreactive IgM antibodies of various specificities, including antibodies against double‐stranded DNA (dsDNA), from AID‐deficient MRL/lpr mice were given to asymptomatic MRL/lpr mice, and the levels of cytokines, proteinuria, immune complex deposition in the kidneys, and glomerulonephritis were examined. Novel AID‐deficient MRL/lpr mice that lack any antibodies were generated for comparison to AID‐deficient MRL/lpr mice that secrete only IgM. Results Treatment with IgM anti‐dsDNA resulted in a dramatic improvement in lupus nephritis. Other autoreactive IgM antibodies, such as antiphospholipid and anti‐Sm, did not alter the pathologic changes. Secretion of proinflammatory cytokines by macrophages and the levels of inflammatory cells and apoptotic debris in the kidneys were lower in mice receiving IgM anti‐dsDNA. Protective IgM derived from AID‐deficient MRL/lpr mice displayed a distinct B cell repertoire, with a bias toward members of the VH7183 family. Conclusion IgM anti‐dsDNA protected MRL/lpr mice from lupus nephritis, likely by stopping the inflammatory cascade leading to kidney damage. A distinct repertoire of VH usage in IgM anti‐dsDNA hybridomas from AID‐deficient mice suggests that there is enrichment of a dedicated B cell population that secretes unmutated protective IgM in these mice.